ESTRO IORT Task Force/ACROP recommendations for intraoperative radiation therapy with electrons (IOERT) in breast cancer. (August 2020) - Fastner, Gerd; Gaisberger, Christoph; Kaiser, Julia; Scherer, Philipp; Ciabattoni, Antonella; Petoukhova, Anna; Sperk, Elena; Poortmans, Philip; Calvo, Felipe A.; Sedlmayer, Felix; Leonardi, Maria Cristina
Highlights: IOERT-Boost should primarily be considered in higher risk patients. Full dose IOERT is one feasible APBI technique for patients with low-risk criteria. For both concepts acute and late toxicities are mild. IOERT does minimally impair cosmetic outcome. Dose prescription and technical prerequisites are well established and described. Abstract: The aim of this review is to provide a comprehensive overview of the role of intraoperative radiation therapy with electrons (IOERT) in breast conserving therapy (BCT), both as partial breast irradiation (PBI) as well as anticipated boost ("IOERT-Boost"). For both applications, the criteria for patient selection, technical details/requirements, physical aspects and outcome data are presented. IOERT as PBI: The largest evidence comes from Italian studies, especially the ELIOT randomized trial. Investigators showed that the rate of in-breast relapses (IBR) in the IOERT group was significantly greater than with whole breast irradiation (WBI), even when within the pre-specified equivalence margin. Tumour sizes >2 cm, involved axillary nodes, Grade 3 and triple negative molecular subtypes emerged as statistically significant predictors of IBR. For patients at low risk for in-breast recurrence (ASTRO/ESTRO recommendations), full dose IOERT was isoeffective with standard WBI. Hence, several national guidelines now include this treatment strategy as one of the standard techniques for PBI in carefully selected patients. IOERT Boost: The largest evidence for boost IOERT preceding WBI comes from pooled analyses performed by the European Group of the International Society of Intraoperative Radiation Therapy (ISIORT Europe), where single boost doses (mostly around 10 Gy) preceded whole-breast irradiation (WBI) with 50 Gy (conventional fractionation). At median follow-up periods up to ten years, local recurrence rates around 1% were observed for low risk tumours. Higher local relapse rates were described for grade 3 tumours, triple negative breast cancer as well as for patients treated after primary systemic therapy for locally advanced tumours. Even in this settings, long-term (>5y) local tumour control rates beyond 95% were achieved. These encouraging results are interpreted as being attributable to utmost precision in dose delivery (by avoiding a "geographic and/or temporal miss"), and the possible radiobiological superiority of a single high dose fraction, compared to the conventionally fractionated boost. IOERT also showed favourable results in terms of cosmetic outcome, assumedly thanks to the small treated volumes combined with complete skin sparing.